The Effect of Service Quality on Inpatient Patient Satisfaction at RSUD Serui, Yapen Islands District - Rinaldo Piris (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine and analyze the effect of service quality on inpatient satisfaction, by taking the research location at the Serui Regional General Hospital (RSUD) Yapen Islands Regency. The sample in this study is the people who use the health services of RSUD Serui, where the number of respondents taken is 115 respondents. The data used in this study is primary data by distributing questionnaires to respondents for responses and through interviews, while secondary data is obtained through various information and important notes from the general administration section of Serui Hospital, Yapen Islands Regency. From the results of the suitability analysis between the level of importance (what is expected by inpatients) and the level of implementation / performance (what is felt by inpatients using the importance analysis method and performance / quality of service (Importence-Performance Analysis), it is found that 1) There is still a gap (gap) between what is expected by the patient (interest) and what is felt by the patient (Implementation/Performance), marked by the average level of conformity for 18 attributes of 73.64% still below 80%, 2 The dimensions that need important attention from Serui Hospital for improvement are assurance, friendliness, courtesy and attention (Empathy), and tangible evidence (Tangible) because these dimensions have not reached the desired target, namely the level of patient satisfaction. New hospitalizations ranged from 64.58% - 74.17%. Meanwhile, other service quality dimensions such as realibilitis (real evidence) and responsiveness (responsiveness) are close to the ideal level of service, which ranges from 78.03 to 79.99 (close to 80% and above).